2008
DOI: 10.1007/s11218-008-9054-2
|View full text |Cite
|
Sign up to set email alerts
|

Social presence in online discussion groups: testing three conceptions and their relations to perceived learning

Abstract: The correlation between three conceptions of social presence (seen as 1. a subjective quality of a medium that determines the quality of the communication and perception of others, 2. self-projection onto the group, and 3. identification with the group) and different aspects of perceived learning in online discussion groups were tested. Six hundreds and fifty nine students completed a web-based questionnaire that was distributed via 50 course Websites. Self projection, perception of others and identification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 49 publications
(46 reference statements)
1
89
1
7
Order By: Relevance
“…These three dimensions are proposed based on prior research (Gefen & Straub 2004;Shen & Khalifa 2009;Caspi & Blau 2008), as well as the interactions involved in actual online purchase processes. Online buyers need to browse information by interacting with the web (SP of web), make sense of other buyers (perception of others), and communicate with the sellers (interaction with sellers).…”
Section: A Multi-dimensional Conceptualization Of Social Presencementioning
confidence: 99%
See 2 more Smart Citations
“…These three dimensions are proposed based on prior research (Gefen & Straub 2004;Shen & Khalifa 2009;Caspi & Blau 2008), as well as the interactions involved in actual online purchase processes. Online buyers need to browse information by interacting with the web (SP of web), make sense of other buyers (perception of others), and communicate with the sellers (interaction with sellers).…”
Section: A Multi-dimensional Conceptualization Of Social Presencementioning
confidence: 99%
“…Online buyers need to browse information by interacting with the web (SP of web), make sense of other buyers (perception of others), and communicate with the sellers (interaction with sellers). Our framework of SP is akin to the conceptualization of SP as "perception of other given the subjective quality of a medium" by Caspi and Blau (2008). They constructed the Medium and Other Perception Scale (MOPS) to cover the SP concept of Short et al (1976).…”
Section: A Multi-dimensional Conceptualization Of Social Presencementioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, perceptual learning is defined as a person to learn the set of beliefs and emotions, is a kind of retrospective evaluation of learning experience [27]. This definition comes from two sources: the cognitive and social-emotional [28].…”
Section: Perceptual Learningmentioning
confidence: 99%
“…Studies have shown that this affective source includes emotions, interests, opinions, attitudes, and values felt during the learning process (L. Anderson & Krathwohl, 2001;Krathwohl, Bloom, & Masia, 1964;Rovai, Wighting, Baker, & Grooms, 2009). Caspi and Blau (2008) suggested that, in retrieving the experience of learning, one may rely on either the cognitive source or the affective source or both. Emotional experiences may be the learning itself but can also serve as an indirect route that forms the experience that learning, in the sense of cognitive change, occurs.…”
Section: Perception Of Learningmentioning
confidence: 99%